An Analysis on Factors Associated with Low Birth Weight (LBW) Incidence in Tentara Wijayakusuma Hospital, Purwokerto - Pety Valeri Amalia; Yektiningtyastuti Yektiningtyastuti (Proceedings Series on Health & Medical Sciences, 2024)
Background: LBW is defined as a baby born with a weight of less than 2,500 grams. LBW is the leading cause of neonatal mortality in Indonesia in 2021 and can lead to growth failure, cognitive development disorders, and chronic illnesses in infants. Objective : To identify the factors associated with LBW incidence in Tentara Wijayakusuma Hospital, Purwokerto, in 2022. Method: This study employed an analytic survey design with a case-control approach and a retrospective view. The study population consisted of all medical records of mothers who gave birth in Tentara Wijayakusuma Hospital in 2022, with a total sample size of 64, including 32 cases and 32 controls. The sampling technique used was total sampling and simple random sampling. Data collection was done using data collection sheets and checklists. The data were analyzed using the Chi-Square test and multiple logistic regression analysis. Results: The study found significant associations between occupation (p=0.043), gestational age (p=0.010), interpregnancy interval (p=0.034), anemia (p=0.001), hypertension (p=0.025), and pregnancy-induced hypertension (p=0.008) with LBW incidence. The multivariate analysis indicated that the most dominant factor was anemia (p=0.000). Conclusion: There are correlations between occupation, maternal age, interpregnancy interval, anemia, hypertension, and pregnancy-induced hypertension with LBW incidence. Anemia is the most dominant factor associated with LBW incidence in Tentara Wijayakusuma Hospital, Purwokerto, in 2022.